Sonic Hedgehog Signaling Activation Promotes Cardioprotective Strategies - Khera, Himanshi; Awasthi, Anupam; Mehan, Sidharth (Current Signal Transduction Therapy, 2020)
Background: Hedgehog pathway plays a crucial role in the neovascularisation and angiogenesis during the embryonic stage in humans. Three genes of hedgehog protein isolated from humans are Sonic hedgehog, Desert hedgehog and Indian hedgehog gene. Two G-protein coupled receptors identified in the sonic hedgehog pathway served as patched receptor and smoothened receptor. Materials and Methods: Particularly, sonic hedgehog gene plays a versatile role in cellular homeostasis and can be a novel therapeutic target in the prevention of cardiovascular disorders. Further various sonic hedgehog modulators have been reported working as futuristic drug molecules in the modulation of cardiovascular dysfunctions. Results: However, there was limited literature availability that has summarized the possible mechanism of targeting Sonic hedgehog signaling pathway. Conclusion: Thus, the present review is aimed at exploring the role of targeting sonic hedgehog protein signaling and modulators as well as to enlighten that how targeting sonic hedgehog protein involves in the amelioration of atherosclerosis, ischemic heart diseases, vascular endothelial dysfunction, heart failure and congenital heart diseases.
Keywords: hedgehog pathway